Enhanced permittivity of negative permittivity middle-layer sandwich polymer matrix composites through conductive filling with flake MAX phase ceramics. Issue 45 (20th July 2020) - Wang, Zhuo; Fan, Jiahao; Guo, Xu; Ji, Jiamin; Sun, Zixiong
Abstract : In this study, a laminated composite with a middle-layer possessing negative permittivity effects was prepared by hot pressing sintering using MAX phase ceramics as a conductive filler. Abstract : Polymer matrix composites are expected to promote the development of embedded packaging technology for circuit boards, but it is still impossible to obtain polymer matrix composites with high permittivity and low loss tangent simultaneously. In this study, a laminated composite with a middle-layer possessing negative permittivity effects was prepared by hot pressing sintering using MAX phase ceramics as a conductive filler. High permittivity (170@1 kHz) and low loss tangent (0.3@1 kHz) were achieved in traditional sandwich polymer matrix composites (SPMCs). Its high permittivity can be explained by the series capacitor model and the interfacial polarization promoted by the flake structure of the MAX phase ceramics. Low loss tangent is guaranteed by the ohmic barrier effect caused by the huge resistance difference between adjacent layers in the composite material. These SPMCs with special structure are expected to provide new ideas for developing embedded capacitors.